Relative hypoxia and oxidative stress in spleen lymphocytes of immunized Balb/c mice as indicated by HIF-1α, HIF-2α, Nrf2 expression, and glutathione peroxidase activity (Faculty of Medicine Universitas Indonesia, 2018)
Background: Lymphocytes activated by immunization must increase their metabolism to meet the energy requirements for mitosis, differentiation, and protein synthesis, which may subject the cell to conditions of relative hypoxia and oxidative stress. This study was conducted to investigate the increase in the levels of transcription factors involved in both conditions.Methods: Male Balb/c mice were divided into the following four groups, each consisting of six animals: the control and three experimental groups. The experimental groups were immunized by injection of 0.2 ml of 2% sheep red blood cells (SRBC) suspended in phosphate-buffered saline (PBS). Lymphocytes were harvested from the spleens of each group at time intervals of 24-, 48-, and 72-h post-immunization. The buffy coat from splenocytes was separated using Ficoll Histopaque as the medium. The lymphocytes were separated from adherent cells by incubating the purified splenocytes in microtubes for 2-h. Cells were lysed by three freeze–thaw cycles (−80°C and 37°C) and used to analyze the levels of HIF-1α and HIF-2α (mRNA and protein), Nrf2 (protein), and glutathione peroxidase (GPx) activity.Results: The treatment caused an increase in GPx activity and HIF-1α protein concentration 24-h post-immunization, whereas the HIF-1α mRNA levels remained static. Elevated Nrf2 protein levels were detected within 48-h after treatment. Meanwhile, the HIF-2α mRNA and protein levels increased within72-h after immunization.Conclusion: Immunization with SRBC suspension induced relative hypoxia, elevated reactive oxygen species (ROS), and oxidative stress in the lymphocytes as indicated by the increase in both HIF-1α and HIF-2α protein and mRNA levels, GPx activity, and Nrf2 protein levels.